EULAR 2023 recommendations for SLE treatment: synopsis for the management of lupus nephritis— the European Renal Association (ERA) — Immunonephrology Working Group (ERA-IWG) perspective - Eleni Frangou; Annette Bruchfeld; Gema M. Fernandez-Juarez; Jürgen Floege; Dimitrios Goumenos; Sarah M. Moran; Stefanie Steiger; Kate I. Stevens; Kultigin Turkmen; Andreas Kronbichler (Počki, 2023)
No abstract